Crazy heart [videorecording (DVD)] - Cooper, Scott, 1970-; Bridges, Jeff, 1949-; Gyllenhaal, Maggie, 1977-; Duvall, Robert; Cobb, Thomas, 1947- (20th Century Fox Home Entertainment, 2010)
The powerful story of a country music star's rocky road to redemption. Bad Blake is a boozy, broken-down singer who reaches for salvation with the help of Jean, a journalist who discovers the real man behind the music. But will Bad's hard-livin' ways and crazy heart cost him his last chance at a comeback?